Lymphoma patients treated with anti-CD20 and chemotherapy display disconnected T and B cell responses to COVID-19 vaccine - Lamure, Sylvain; Chavez, Houria Hendel; de Goër de Herve, Marie-Ghislaine; Fornecker, Luc-Matthieu; Drenou, Bernard; Jacquet, Caroline; Merabet, Fatiha; Kohn, Milena; Quélin, Florence; Jackson, Angela; Choquet, Sylvain; Duléry, Rémy; et al. (Frontiers in Immunology, 2025)
Due to immunosuppressive treatment, COVID-19 vaccination is challenging in patients with B-cell lymphoma. We prospectively evaluated CD4, CD8 T-cell and serological responses to the COVID-19 mRNA vaccine in a cohort of patients treated for a B-cell lymphoma with anti-CD20 therapy. During lymphoma treatment, CD4, CD8, and CD19 cell dropped. While functional-specific CD4 and CD8 T-cell responses to SARS-CoV-2 were unaffected, vaccination in patients on treatment induced low specific antibody titers, contrasting with a preserved serological response when vaccination was completed before treatment initiation. Those findings reinforce a vaccinal strategy based on completion before lymphoma treatment, with a booster administered afterward.